Broadcast authentication algorithm for wireless sensor networks - YAO Xuan-xia; ZHENG Xue-feng; ZHOU Xian-wei (Tongxin xuebao)
In order to authenticate the broadcast data in wireless sensor networks efficiently,a broadcast authentication algorithm based on the properties of one-way,quasi-commutative and absorbency in Nyberg’s fasting one-way accumulator was put forward.The MACs computed by hashing the broadcast data with the shared key between the broadcaster and each scheduled receiver were used to be the accumulative items in this algorithm.The detailed analyses in the aspects of the security,anti-captured and costs show that the proposed broadcast authentication algorithm can authenticate the random broadcast data immediately in small area and meet the essential requirements for broadcast authentication in wireless sensor networks.